2014
DOI: 10.5152/ucd.2014.2284
|View full text |Cite
|
Sign up to set email alerts
|

Our results of lower gastrointestinal endoscopy: evaluation of 700 patients

Abstract: Objective: Although radiological imaging modalities like barium enema and computed tomography provide some clues, endoscopic methods still maintain superiority in assessment and differential diagnosis of large intestinal symptoms and complaints that require biopsy. We aimed to present the results of colonoscopic procedures performed in our general surgery clinic in detail. Material and Methods:Seven hundred patients who presented to Afyon Kocatepe University, Faculty of Medicine, Department of General Surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…The CIR reported by retrospective studies without enhanced patient education is similar to our CG. CIR was 73.4% in one of these studies and 61% in the other 10 , 31 . In another retrospective study, CIR was reported to be 72.1% and 75.4% in patients whose bowel cleansing was evaluated as moderate and poor, respectively 32 .…”
Section: Discussionmentioning
confidence: 68%
“…The CIR reported by retrospective studies without enhanced patient education is similar to our CG. CIR was 73.4% in one of these studies and 61% in the other 10 , 31 . In another retrospective study, CIR was reported to be 72.1% and 75.4% in patients whose bowel cleansing was evaluated as moderate and poor, respectively 32 .…”
Section: Discussionmentioning
confidence: 68%
“…The CIR reported by retrospective studies without enhanced patient education is similar to our CG. CIR was 73.4% in one of these studies and 61% in the other (10,31) .…”
Section: Discussionmentioning
confidence: 72%
“…El ICR de estudios retrospectivos que no suministraron la educación perfeccionada a los pacientes, presentan resultados similares al GC de este estudio. El ICR encontrado en esos estudios fue de 73.4% y 61% (10,31) .…”
Section: Discussionunclassified